Generic and vague uses of a second-person singular pronoun in an open-class person-reference system and speaker creativity in reported speech: the case of anata in Japanese - Yonezawa Yoko (Linguistics)
This study analyzes hitherto neglected uses of a second-person singular (2sg hereafter) pronoun in Japanese: the ‘generic’ and ‘vague’ uses of the 2sg pronoun anata observed in reported speech. The aim of the study is twofold. First, it refutes the broader assumption in typological studies that languages with an open-class pronominal system, such as Japanese and Korean, do not allow generic uses of 2sg (Kitagawa and Lehrer 1990. Impersonal uses of personal pronouns. Journal of Pragmatics 14(5). 739–759). This study demonstrates that the 2sg pronoun anata in Japanese is used to refer to people in general (‘generic’ use) or to human referents who are low in specificity (‘vague’ use). Second, as these uses occur in reported speech, this study sheds light on the various ways in which current speaker attitudes in reported speech may be encoded across different languages (Spronck 2012. Minds divided: Speaker attitudes in quotatives. In Isabelle Buchstaller & Ingrid van Alphen (eds.), Quotatives: Cross-linguistic and cross-disciplinary perspectives, 71–142. Amsterdam: John Benjamins: 87). Drawing on the notion of ‘constructed dialogue’ (e.g., Tannen 1989. Talking voices: Repetition, dialogue, and imagery in conversational discourse. Cambridge: Cambridge University Press), the study shows that these uses of anata are most often the quoting speaker’s ‘construction’ rather than ‘report’, reflecting the quoting speaker’s attitude in specifying the referent. Using the data obtained from parliamentary debates, the study demonstrates that politicians draw on these uses of anata as one of their speech strategies for creating generalized narratives.